Pengaruh Aktivitas Masyarakat Pesisir Terhadap Kondisi Ekosistem Mangrove di Pantai Desa Sialang Buah KecamatanTeluk Mengkudu Kabupaten Serdang Bedagai - Ade Artia Gultom; Darma Bakti; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
Sialang Buah village on the coastal areas that the population dominantly depent on the potential of the region for living, such as fishing, fish farming, settlement and the place tourism. There are problems from exploiting activities on the Sialang Buah village’s potential that affect the condition and existance of coastal ecosystem espencially mangrove. This research aims to determine the effect of community activities againts mangrove ecosystem condition at Sialang Buah village. It was conducted from may to june 2016. The transformation from structure of the land can be seen by the RGB on satelite imagery of Landsat 7 TM and Landsat 8 using Er Mapper 7.1 and arcgis 10, other than that, the sampling data was helped by questionnaries and interviews on public and tourists with purposive respondent, also using the socioeconomic survey method which is total value of scoring (TNS), the result showed that the land change are happend since 2003 to 2016, TNS obtained from socioeconomic factor is 200 indicating the factor influance the destruction of mangrove forest.Keywords: Community Activities, Coastal Communities, Mangrove, Sialang Buah Village